KAJIAN PADA KEMAMPUAN SISWA TAHUN KEDUA SMA SETIA DHARMA PEKANBARU DALAM MENULIS TEKS NARATIF - Welda, Mila; Gultom, Effendy; ', Hadriana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research was conducted to find out the ability of the second year students of SMA Setia Dharma Pekanbaru in writingÂ narrative texts. The population of the study were 50 second year students of Social Science and Exact Science classes. The instrument for collecting the data was a written test. Based on the writing results, the studentsâ€™ ability is in good level (68.1).Â